The development of stress management model among nursing students in private higher education institutions - Taewaphokinkul, Muntana; Virutsetazin, Kamonmarn (Edelweiss Applied Science and Technology, 2024)
The research on developing a stress management model for nursing students at private higher education institutions aims to create an effective stress management approach. This study applies the concepts of Health-Related Hardiness and Resilience using a research and development methodology divided into three phases, 1) Synthesis of a draft prototype: In this phase, an initial stress management model was conceptualized. 2) Development of the stress management prototype: The finalized prototype comprises three main concepts and five activities, Concept 1: Self-commitment – Strive for Success (Activities: Motivation and Opportunity), Concept 2: Internal and External Control – Finding Solutions (Activities: Novelty and Encourage) and Concept 3: Facing Challenges, I Can Do It (Activity: Yourself). 3) Effectiveness testing of the prototype: This phase involved a trial with 30 experimental participants and 30 in a comparison group. Results showed a statistically significant reduction in stress levels within the experimental group before and after the intervention (t = 24.286, p < .001). Post-intervention stress levels were significantly lower in the experimental group compared to the comparison group (t = -12.079, p < .001). Overall resilience in the experimental group also showed a statistically significant improvement after the intervention (t = -9.761, p < .001), with increases across all three dimensions of resilience and The resilience levels of the experimental group were significantly higher than those of the comparison group (t = 1.829, p < .001). The researcher developed this stress management model to enhance health-related hardiness and psychological resilience among nursing students, naming it the MONEY MODEL.